The impact of carbon prices on renewable energy support - Jan Abrell; Mirjam Kosch (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
This paper examines how optimal renewable energy (RE) support (RES) policies need to be adjusted to account for carbon prices. We show theoretically and empirically that changing carbon prices requires adjusting RE production subsidies due to two different motives: First, RE premiums need to be reduced to reflect the carbon value embedded in the market price. Second, RE premiums and feed-in tariffs need to be adjusted once a fuel switch away from coal towards gas power occurs. This adjustment is necessary to account for changes in the marginal external benefit of RE. For the case of the UK, we estimate the optimal RE subsidies and their adjustments due to a fuel switch. Furthermore, we use numerical simulations to analyze the impact of varying carbon prices on optimal RES. We show that the necessary adjustment due to a fuel switch is empirically rather small, whereas RE premiums must be phased out with increasing carbon prices due to the increasing reflection of the carbon cost in the electricity market price. Finally, a fuel switch increases solar-induced abatement, whereas it wind-induced abatement is rather invariant to a fuel switch. Yet, the differentiation of RE subsidies between wind and solar power is modest.
Keywords: Q41; Q42; Q58; 330; Renewable promotion; Carbon pricing; Electricity generation